TOTAL AUDIT REPORT LAG: PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN - Chrystalia, Chrystalia; Apriwenni, Prima; Esra, Martha Ayerza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Financial statements are one of the primary references for evaluating a company's performance. These reports generally need to be prepared quickly because they are crucial for companies, especially those that are publicly traded. The Indonesia Stock Exchange requires publicly traded companies to provide accurate and timely data and information. The purpose of this research is to determine whether profitability, leverage, and company size have an impact on audit report lag. The sample used in this study consists of companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sampling method applied is purposive sampling method, with several criteria used so as to get a sample of 47 companies with a research period of 4 years. The data analysis technique used is pooling test, descriptive statistical test, classical assumption test, multiple linear regressioin analyst, and hypothesis testing. The test which is processed using the IBM SPSS Statistic 27 application. It can be concluded that there is sufficient evidence that profitability has a negative effect on audit report lag. Leverage has a negative effect on audit report lag, and there is not enough evidence that company size has a positive effect on audit report lag.